2007
DOI: 10.2337/db06-0738
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea Compounds Uncouple the Glucose Dependence of the Insulinotropic Effect of Glucagon-Like Peptide 1

Abstract: Glucagon-like peptide (GLP)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 53 publications
1
69
1
1
Order By: Relevance
“…Also in line with these studies, no effect of GLP-2 on insulin secretion was observed. It is well established that somatostatin inhibits glucagon secretion in the endocrine pancreas, and we have recently shown that GLP-1 mediates its inhibitory effect on the pancreatic alpha cell through somatostatin acting on somatostatin receptor subtype 2 (J. de Heer, D. H. Coy, J. J. Holst, unpublished results) [19][20][21]. However, in the present study the release of somatostatin was unaltered in response to GLP-2.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Also in line with these studies, no effect of GLP-2 on insulin secretion was observed. It is well established that somatostatin inhibits glucagon secretion in the endocrine pancreas, and we have recently shown that GLP-1 mediates its inhibitory effect on the pancreatic alpha cell through somatostatin acting on somatostatin receptor subtype 2 (J. de Heer, D. H. Coy, J. J. Holst, unpublished results) [19][20][21]. However, in the present study the release of somatostatin was unaltered in response to GLP-2.…”
Section: Discussioncontrasting
confidence: 56%
“…injection of pentobarbital (50 mg/kg), and the pancreas was dissected and perfused in situ as described in [21]. Briefly, the rat was killed by removal of the heart and the pancreas was perfused in a single-pass system through both the coeliac and the superior mesenteric artery via a catheter inserted into the adjacent abdominal aorta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, co-administration of GIP with a sulfonylurea restores pancreatic beta cell sensitivity to GIP [7], although this could be linked to uncoupling of incretin glucose dependency by sulfonylureas [8]. More encouraging, recent studies have highlighted the possibility that xenin, a hormone co-secreted with GIP from a subset of enteroendocrine K cells, could amplify the insulin-secretory response of GIP [9].…”
Section: Introductionmentioning
confidence: 99%
“…For GIP, the first 14 N-terminal amino acid residues contain the bioactive domain important for insulin-secretory function [25,26]. Based on this knowledge, we constructed a novel GIP/xenin hybrid peptide, (DAla 2 )GIP/xenin-8-Gln, by linking GIP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) to xenin-8-Gln, retaining the regions of each peptide known to be important for biological activity (see electronic supplementary material [ESM] Table 1). Importantly, since GIP is a substrate for dipeptidyl peptidase-4 (DPP-4) [27], the hybrid peptide includes substitution of the naturally occurring alanine L isomer residue by a D isomer at position 2 [28,29].…”
Section: Introductionmentioning
confidence: 99%